Synthesis and characterization of photoactivatable doxycycline analogues bearing two-photon-sensitive photoremovable groups suitable for light-induced gene expression - Goegan, Bastien; Terzi, Firat; Cambridge, Sidney (ChemBioChem, 2018)
We report the synthesis and photolytic properties of caged 9-aminodoxycycline derivatives modified with 2-4′-bis-[2-(2methoxyethoxy)ethyl]-4-nitrobiphenyl-3-ylprop-1-oxy (EANBP) and PEG7-ylated (7-diethylamino-2-oxo-2H-chromen-4-yl)methyl (PEG7-DEACM) groups. 9-Aminodoxycycline is a tetracycline analogue capable of activating transcription through the inducible TetOn transgene expression system and can be regioselectively coupled to two-photon-sensitive photo-removable protecting groups by carbamoylation. The EANBP-based caged 9-aminodoxycycline showed complex photochemical reactions but did release 10 % of 9-aminodoxycycline. However, 9-(PEG7-DEACMamino)doxycycline exhibited excellent photolysis efficiency at 405 nm with quantitative release of 9-aminodoxycycline and a 0.21 uncaging quantum yield. Thanks to the good two-photon sensitivity of the DEACM chromophore, 9-aminodoxycycline release by two-photon photolysis is possible, with calculated action cross-sections of up to 4.0 GM at 740 nm. Therefore, 9-(PEG7-DEACMamino)doxycycline represents a very attractive tool for the development of a light-induced gene expression method in living cells.